A constitucionalização dos direitos humanos no Brasil - Valentim, Aline Medeiros Vasconcelos (2007)
This work intends to analyze how the Brazilian constitutional system handles the protection of human rights, focusing on the inclusion in our current legislation of the rules and guarantees issued by international treaties and conventions that deal with this matter. Based on the study of the modifications implemented by 45/2004 Amendment, we seek to demonstrate that the changes concerning the incorporation of international rights into the national law, which were inserted in the constitutional text in order to fulfill a growing preoccupation with the efficiency of the mechanisms for the protection of human rights, contributed little or nothing to the solution of the problem of the effectiveness of those rights. Far from representing an obstacle only to our system, the low effectiveness of the protection of human rights is a deficiency noticed worldwide. Despite the modern and advanced legal apparatuses, the courts responsible for ensuring the observance of those rights are still applying them very timidly.